Benefits of Veterinary Herd Health Management on German Dairy Farms: Status Quo and Farmers' Perspective - Ries, Jenny; Jensen, Katharina Charlotte; Müller, Kerstin-Elisabeth; Thöne-Reineke, Christa; Merle, Roswitha (Frontiers in Veterinary Science, 2022)
Veterinary Herd Health Management plays an important role in veterinary medicine on dairy farms and has also been mandatory at the European Union level since April 21, 2021. Despite the increasing importance of VHHM, little is known about the extent of utilization of VHHM by dairy farmers and their view on this type of collaboration. Therefore, this cross-sectional study aimed to determine the status quo of the currently practiced VHHM in Germany. For this purpose, an online survey was conducted among dairy farmers in November and December 2020. From 216 analyzed questionnaires, about half (n= 106) of the surveyed dairy farmers used VHHM at different scopes. However, regardless of the group, the term “veterinary herd health management” generally was given most relative importance by the participants as a veterinary service for herd fertility improvement, rather than the actual definition of a holistic approach. In contrast to this, the actual motivation of the VHHM participants, to take part in such a program was primarily based on the desire to safeguard animal health by employing preventive measures, that is, to avoid the occurrence of diseases via improved management and to improve farm performance (and profitability). Dairy farmers who opted for VHHM tended to manage larger higher yielding herds than those who did not. Additionally, the farmers in latter farms were more likely to make joint animal health decisions with their veterinarians. Using a latent class analysis, two groups of farmers among farms that were not currently using VHHM were identified, one of which expressed great interest in using VHHM while the other did not. Since the new legal basis makes the topic even more relevant than before, dairy farmers, animals, and veterinarians might benefit from the study to exploit hidden opportunities for VHHM collaboration.